2014
DOI: 10.1186/1472-6963-14-212
|View full text |Cite
|
Sign up to set email alerts
|

“Not too far to walk”: the influence of distance on place of delivery in a western Kenya health demographic surveillance system

Abstract: BackgroundMaternal health service coverage in Kenya remains low, especially in rural areas where 63% of women deliver at home, mainly because health facilities are too far away and/or they lack transport. The objectives of the present study were to (1) determine the association between the place of delivery and the distance of a household from the nearest health facility and (2) study the demographic characteristics of households with a delivery within a demographic surveillance system (DSS).MethodsCensus samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…Likewise, a 2014 study in rural India reported a 4.4% decrease in the probability of institutional delivery for each additional kilometer to the closest health facility (Kumar et al 2014). Other recent studies have reported similar findings (Gabrysch et al 2011;Mwaliko et al 2014). Although our pooled analysis found that higher travel time decreased the likelihood of institutional delivery, country-specific analyses revealed that this was the case only in Guatemala.…”
Section: Discussionsupporting
confidence: 74%
“…Likewise, a 2014 study in rural India reported a 4.4% decrease in the probability of institutional delivery for each additional kilometer to the closest health facility (Kumar et al 2014). Other recent studies have reported similar findings (Gabrysch et al 2011;Mwaliko et al 2014). Although our pooled analysis found that higher travel time decreased the likelihood of institutional delivery, country-specific analyses revealed that this was the case only in Guatemala.…”
Section: Discussionsupporting
confidence: 74%
“…Factors identified in this study may differ from other city where there is a lack of health facilities. Several studies show that the distance to the health facility is a predictor of home treatment [51, 52], of access appropriate and effective health care [53] and also of childhood mortality [54]. It was found in this study that financial means was a factor associated with children home treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Other studies show distance to be a significant factor that affects choice of birthplace [18, 19]. In this study, the most common participant recommendation to increase institutional service utilization was to improve ambulance accessibility and currently only a minority of those who gave birth at an institution arrived via an ambulance.…”
Section: Discussionmentioning
confidence: 74%